Electrochemical Approach to Evaluate the Wettability of Rough Surfaces. (4th January 2017) - Zahiri, Beniamin; Sow, Pradeep Kumar; Haow Kung, Chun; Mérida, Walter
Abstract : Surface wettability is usually determined based on the optical measurement of the contact angle. Theoretical models show that this contact angle depends on the solid-liquid interaction under the droplet, which is optically inaccessible. Here, we present an electrochemical method for evaluating the wetted area under the droplet for a rough surface. The experimental approach includes simultaneous measurement of the contact angle and the electrochemical capacitance. We have shown the capability of this method for a series of carbonaceous surfaces with varying roughness. The experimental results have been correlated to the Wenzel and Cassie-Baxter wettability theories. This approach is applicable for irregular roughness features and can be used to study the wetting behavior of different surface structures. We believe this work can be applied to design characterization tools that facilitate the development of mechanistic and predictable mathematical models for wettability of rough surfaces.